ASSESSMENT OF ROLL AND PITCH CONTROL OF UTM JAGADRONE (Journal of Transport System Engineering, 2023)
This paper aims to quantify the flying qualities of UTM JagaDrone using autonomous and semi-autonomous PID tuning. Drone technology has grown in popularity worldwide due to its applications, notably in security and surveillance. The JagaDrone is completely autonomous aerial surveillance, and this first aerial responder is equipped with an emergency stream video while flying to avoid obstacles and track a target. We conducted the tuning process using an open-source ArduPilot Mission Planner, and the tuned PID value was tested by carrying out numerous flight tests. In general, the flight testing of JagaDrone has unique aspects caused by the absence of a pilot onboard and the reduced reliability of the system. The flight test aims to ensure the JagaDrone is manufactured properly and in a condition for safe operations. This paper presents an experimental validation of multicopters to determine the desired tune method for the PID controller applied for multicopters. From the tuning, it was found that the significant overshoot and the settling time were reduced by 50%, which shows an improvement in the stability of a multicopter. Thus, the proposed method is valid and can be used as a reference for multicopter tuning. The result proves that the method used in this experiment produces a stable tune for a multicopter. The method proposed in this paper can be used to carry out both autonomous and semi-autonomous PID tuning.
Keywords: JagaDrone; hexacopter; tuning